2016
DOI: 10.1158/0008-5472.can-15-3034
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Induced Systemic Inflammation Is Driven by Upregulation of Toll-Like Receptor TLR4 and Endotoxin Leakage

Abstract: Doxorubicin is one of the most effective chemotherapeutic agents used for cancer treatment, but it causes systemic inflammation and serious multiorgan side effects in many patients. In this study, we report that upregulation of the proinflammatory Toll-like receptor TLR4 in macrophages by doxorubicin is an important step in generating its toxic side effects. In patient serum, doxorubicin treatment resulted in leakage of endotoxin and inflammatory cytokines into circulation. In mice, doxorubicin damaged the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
101
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 43 publications
10
101
3
1
Order By: Relevance
“…can protect rats from Doxo-induced inflammation, cardiac fibrosis and damage, and from I/R heart injury. It is well known that Doxo can cause toxicity and inflammation in several organs, including the heart, liver and intestine (39,54). In particular, Doxo can cause the release of proinflammatory cytokines in the blood of patients, such as IL-1b and TNF-a (39), and the release of ROS, cTnT, and LDH, markers of cytotoxic and cardiotoxic responses (1,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…can protect rats from Doxo-induced inflammation, cardiac fibrosis and damage, and from I/R heart injury. It is well known that Doxo can cause toxicity and inflammation in several organs, including the heart, liver and intestine (39,54). In particular, Doxo can cause the release of proinflammatory cytokines in the blood of patients, such as IL-1b and TNF-a (39), and the release of ROS, cTnT, and LDH, markers of cytotoxic and cardiotoxic responses (1,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Doxo can cause toxicity and inflammation in several organs, including the heart, liver and intestine (39,54). In particular, Doxo can cause the release of proinflammatory cytokines in the blood of patients, such as IL-1b and TNF-a (39), and the release of ROS, cTnT, and LDH, markers of cytotoxic and cardiotoxic responses (1,(40)(41)(42). In the heart, inflammation is stimulated by Doxo-induced cell apoptosis and tissue damage; this effect involves the activation of the TNF signaling pathway, the generation of massive ROS, and the persistent expression of multiple proinflammatory cytokines such as IL-1b and TNF-a (39,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of bacterial LPS by toll‐like receptor 4 (TLR4) is known to trigger a cascade of cellular signaling to induce inflammation. In fact, it is demonstrated that overexpression of TLR4 promotes systemic inflammation and intestinal neoplasia in mice . Compelling evidence indicates that elevated inflammation constitutes a major mechanistic link between obesity and increased tumor risk .…”
mentioning
confidence: 99%
“…Despite the fact that DOX is one of the first line agents in cancer therapy, its serious side effects including haematological, cardio‐ and nephrotoxicity limit its conventional uses . There is a recent report indicating a DOX‐induced systemic inflammation due to leakage of endotoxin into the circulation and consequently enhancement of TLR‐4 signalling . In paediatric practice, DOX is used to treat the testicular tumours, which may also cause testicular dysfunction, characterized by cellular apoptosis‐related damages …”
Section: Introductionmentioning
confidence: 99%